Currency Risk and Management Methods in Lithuanian Companies - Bagdonienė, Renata (Ekonomika, 1999)
This article investigates currency risk problem. This problem becomes more apparent when the Litas will be related with currency basket, which includes EURO and USD according to 1997–1999 monetary policy Bank of Lithuania.The internal and external ways of currency risk management ways, counting methods of derivative financial means are also discussed in this article.Some recommendations how companies can minimize currency risk under existing conditions in Lithuania are provided.